ANALISIS AKTIVITAS ANTI OKSIDAN FLAVONOID DAUN EKOR NAGA (RHAPIDHOPHORA PINNATA SCHOTT) DENGAN DOSIS BERTINGKAT TERHADAP HEMATOKRIT DAN KADAR HB MUS MUSCULUS BABLC ALBINO JANTAN YANG DIBERI PAPARAN ASAP ROKOK - Dilla Mahdalena (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2020)
Background: Cigarette smoke is a source of free radicals. If inhaled, its activity can damage the structure of erythrocyte membrane function which affects the decrease in hemoglobin and hematocrit. The influence of free radicals can be suppressed through the administration of antioxidants. Dragon tail leaves contain phenolic compounds in the form of polyphenols which are antioxidants. Objective: To determine the effect of administration of dragon tail leaf extract (rhapidhophora pinnata schott) with multilevel doses on hemoglobin levels and hematocrit of blood of mice exposed by cigarette smoke. Method: The method used was an experimental method with a Post Test Control research design. The Design Group used the Mus Musculus Bablc albino male which was divided into 4 groups. The control group, P1 at a dose of 50mg / kgBB, P2 at a dose of 100mg / kgBB, P3 at a dose of 150mg / kgBB with 1 cigarette / day for 14 days. This research was conducted on May 22-June 5, 2019 in the Anatomy Fisiology Stikes Piala Sakti Pariaman. Results: The results of data analysis using one way ANOVA revealed that the administration of dragon tail leaf extract dose had a significant effect between hemoglobin and hematocrit levels with a P-value of 0,000. Conclusion: Based on the results of this study it can be concluded that the antioxidant content of flavonoids found in leaves (Rhapidhophora Pinnata Schott) can increase hemoglobin and hematocrit levels. And it is necessary to do further testing on humans as an effort to test the safety of doses